PENGARUH PENGGUNAAN VARIASI SISTEM PENGAPIAN & VARIASI PENGGUNAAN BAHAN BAKAR DENGAN KADAR RON BERBEDA TERHADAP KONSUMSI BAHAN BAKAR PADA ENGINE TOYOTA 5K - Dhimas Aji Priyatmoko; Kurniawan Joko Nugroho; Muhamad Amiruddin, M.Pd. (Journal of Automotive Technology Vocational Education, 2025)
This study aims to determine the fuel consumption efficiency of Pertalite, Pertamax, and Pertamax Turbo in a Toyota 5K engine with two ignition systems, namely the conventional system and the CDI (Capacitor Discharge Ignition) system. The test was conducted at a constant engine speed of 1500 rpm for 5 minutes, with the engine mounted on an engine stand without a charging system (alternator), causing the battery voltage to decrease over time. The CDI system, which depends on stable voltage, showed incomplete combustion results when the voltage decreased, while the conventional ignition system was still able to work properly. The results of the study show that conventional ignition systems are more efficient than CDI in terms of fuel consumption. The lowest fuel consumption was recorded when using Pertamax Turbo with conventional ignition (130 ml), while the highest consumption occurred when using Pertalite with CDI ignition (160 ml). The largest difference in consumption occurred with Pertamax Turbo fuel, at 13 ml between the two ignition systems. These results indicate that fuel efficiency is influenced by the suitability of the ignition system to electrical conditions and fuel characteristics.   Keywords: Toyota 5K engine, CDI ignition system, and conventional ignition.